1978
DOI: 10.1021/es60143a007
|View full text |Cite
|
Sign up to set email alerts
|

Fate of polycyclic aromatic hydrocarbons in controlled ecosystem enclosures

Abstract: Prudhoe crude oil enriched with a number of polycyclic aromatic hydrocarbons was added as a dispersion to a controlled ecosystem enclosure suspended in Saanich Inlet, Canada. Concentrations of various aromatics were determined in water, zooplankton, oysters, and bottom sediments. Initial water concentrations of the lower weight aromatics, naphthalenes and anthracene, were 10-20 gg/L, whereas the initial concentrations of benzo(a)pyrene, benz(a)anthracene, and fluoranthene ranged from 1 to 6 ag/L. These concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(48 citation statements)
references
References 12 publications
6
41
0
1
Order By: Relevance
“…It was not surprising that chrysene and benzo(a)pyrene were below detection limits in tissue homogenates since these PAHs are not frequently detected in marine organisms exposed to petroleum contaminants. Naphthalene and naphthalene derivatives, however, have been detected with more frequency (Lee et al 1978;McDonald et al 1992;. It is possible that the parent PAHs present in our exposure water were taken up and rapidly metabolized.…”
Section: Discussionmentioning
confidence: 96%
“…It was not surprising that chrysene and benzo(a)pyrene were below detection limits in tissue homogenates since these PAHs are not frequently detected in marine organisms exposed to petroleum contaminants. Naphthalene and naphthalene derivatives, however, have been detected with more frequency (Lee et al 1978;McDonald et al 1992;. It is possible that the parent PAHs present in our exposure water were taken up and rapidly metabolized.…”
Section: Discussionmentioning
confidence: 96%
“…Naphthalenes are volatiles and are more soluble than phenanthrenes and dibenzothiophenes. Furthermore, naphthalene degradation has been reported in waters from pristine and oil-contaminated ecosystems (Lee et al, 1978, Herbes and Schwall, 1978, Lee and Ryan, 1983, Massie et al, 1985. Naphthalene is relatively water soluble (31.2 mg L À 1 ) and has such a high vapor pressure (0.23 mmHg) that biodegradation and volatilization in open waters may be important processes that affects its fate in aquatic systems.…”
Section: Bivalve Tissuementioning
confidence: 99%
“…In a study by Kowalewska (23), phytoplankton cells significantly contributed to the transport of PAHs from the upper layers of the Southern Baltic ecosystem to the sea floor by sedimentation. Although the hydrophobic nature of PAHs (log K ow ϭ 3 to 8) greatly limits their solubility in seawater, this property would favor their adsorption to marine particulate matter, including phytoplankton and detritus (11,27). Kowalewska (23) quantitatively demonstrated that different PAH compounds conferred different correlation coefficients for binding to phytoplankton cells.…”
mentioning
confidence: 99%